SUPPLEMENTATION WITH PELLETED STINGING NETTLE IMPROVES HEMATOLOGICAL PARAMETERS, AND REDUCES TOTAL PARASITE LOAD AND GUT ESCHERICHIA COLI COUNTS IN PASTURED GOATS - E. Ndegwa; V. Temu a; L. Rutto b (Journal of Animal and Plant Sciences, 2023)
Stinging nettle (Urtica dioica), is widely consumed as a vegetable in many parts of the world and also touted for many health benefits. Although the nutritional value has been known and medicinal value purported for years, research findings are scarce on its value to ruminants. This study evaluated the hematological and gut health benefits of supplementing pelleted stinging nettle to pastured yearling goats for twelve weeks. Overall health, hematocrit, total serum protein, and anemia scores using (FAffa MAlan CHArt) FAMACHA© scoring system were evaluated. Total gut parasite load was determined by both fecal egg count and molecularly using a PCR protocol. Total fecal Escherichia coli, Bifidobacterium and Lactobacillus spp were also determined molecularly. Overall, pelleted stinging nettle was highly palatable to goats and no negative health effects were detected in supplemented goats. Nettle supplemented goats exhibited significantly increased hematocrit, FAMACHA© scores, and decreased total parasite load. A significant decrease in total gut E. coli in the supplemented goats was also detected. The Bifidobacterium and Lactobacillus spp counts were very low in all goats irrespective of treatment group. These findings indicate potential of stinging nettle pellets in circumventing the negative health impacts of Hemonchus contortus and other gut parasites while reducing the potential gut microbial pathogen loads. Thus stinging nettle seems a good candidate for further research on potential use as a bioactive feed supplement for ruminants.
Keywords: Stinging nettle; supplement; goats; hematocrit; FAMACHA©; Hemonchus contortus; parasites; E. coli